A study of the effectiveness of training program in Pejabat Setiausaha Kerajaan Pahang based on employees' perceptions / Nurul Syahida Salihin - Salihin, Nurul Syahida (2016)
The purpose of this study is to identify the effectiveness of training program in Pejabat Setiausaha Kerajaan Pahang. This study investigates the most use of training techniques either of information distribution technique, simulation technique or on-the-job training technique. The questionnaires had been distributed randomly to the employees in Pejabat Setiausaha Kerajaan Pahang who are Malaysian. The respondents for this study were 55 respondents, but only 48 respondents were selected to be used to find the findings based on Krejcie & Morgan table from a given population. After collected the questionnaires from the respondents, the data had been analyzed by using Statistical Packages for the Social Sciences (SPSS) version 20 to get the results. Based on the findings, most of respondents choose on-the-job training technique as the mostly training program practiced in Pejabat Setiausaha Kerajaan Pahang. The findings also show that the level of the effectiveness of training program is good. The researcher suggested that simulation training technique also should be used to train employees by using advance technology besides it can improve the employee's skills and knowledge.